Effect of sprouting on nutritional quality of pulses. (2nd January 2019) - Erba, Daniela; Angelino, Donato; Marti, Alessandra; Manini, Federica; Faoro, Franco; Morreale, Federico; Pellegrini, Nicoletta; Casiraghi, Maria Cristina
Abstract: In order to investigate the nutritional quality of industrial-scale sprouted versus unsprouted chickpeas and green peas, before and after cooking, the ultrastructure, chemical composition, antioxidant capacity, starch digestibility, mineral content and accessibility were analysed. Sprouting did not deeply affect raw seed structure, although after cooking starch granules appeared more porous and swelled. Chemical composition of raw sprouted seeds was not strongly affected, excepting an increase in protein (both pulses), and in free sugars (in peas; +10% and +80%, respectively, p < .05). The industrial sprouting favoured phytic acid leaching in cooking water (−35% in seeds, compared to unsprouted cooked ones, p < .05), and promoted antioxidant capacity reductions in raw and cooked seeds (−10% and −37%, respectively, p < .05). In conclusion, sprouting on an industrial-scale induced mild structural modifications in chickpeas and peas, sufficient to reduce antinutritional factors, without strongly influencing their nutritional quality. These products could represent nutritionally interesting ingredients for different dietary patterns as well as for enriched cereal-based foods.